Can e-learning replace classroom learning? - Zhang, Dongsong; Zhao, J. Leon; Zhou, Lina; Nunamaker, Jay F. (ACM, 2004)
In an e-learning environment that emphasizes learner-centered activity and system interactivity, remote learners can outperform traditional classroom students.
Keywords: Applied computing; Education; Social and professional topics; Professional topics; Computing education; Computing education programs; Computer science education; Information science education